Kurdish Women Activists’ Conceptualisation of Feminism and Nationalism: An Ethnographic Study of London-Based Kurdish Organisations - ALTIN SORAN, Berrin (2023)
This study has explored the ways in which Kurdish women activists interpret and practise feminism and nationalism in London. Kurdish women’s relations to nationalism can be analysed in various ways. However, this study specifically focuses on the claim that nationalism is antithetical to feminism. Moreover, it has argued that the pre-migration experiences of Kurdish women, related to their national and gender identities, direct them to continue their activism in London. Accordingly, I asked: what roles did the pre-migration experiences of Kurdish women play in their identities and their engagement with activism in London? In what ways do Kurdish women activists in London articulate their political and social demands? How do these women activists negotiate feminism and nationalism?